Efficacy and Safety of Apremilast versus Methotrexate in the Treatment of Chronic Plaque Psoriasis (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Psoriasis is a common, chronic, inflammatory and proliferative disease of the skin, also affecting nail and joints. Although there are a range of treatment options available, none have proved to wane the symptoms fully and also they reappear in course of time.Aim: To explore the safety and efficacy of Apremilast and Methotrexate on chronic plaque psoriasis patients.Methods: A randomized open clinical trial was done among fifty clinically diagnosed chronic plaque psoriasis patients in the Department of Dermatology and Venereology at Combined Military Hospital (CMH), Dhaka from 1st July 2017 to 30th June 2018. Patients were divided randomly into two equal treatment groups, 25 for Methotrexate and 25 for Apremilast. Involvement of body surface by plaque psoriasis, erythema, scaling and induration were recorded in a 3 points scale before treatment and 8 weeks after starting the treatment and finally at 12th week.Results: Reduction of psoriasis at 1st follow up in Methotrexate and Apremilast groups were 29.9±9.0 and 31.9±11.6 respectively and at 2nd follow up were 85.9±7.3 and 28.48±39.3 respectively. Significantly higher improvements were observed in Methotrexate group than Apremilast group both at 1st and 2nd follow up (p=0.001).Conclusion: Methotrexate is a better therapeutic option than Apremilast in the treatment of chronic plaque psoriasis.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 39-41